Fabrication of SERS Substrates Using Au Nanoparticles Prepared by Laser Ablation in Distilled Water and Detection of Tetracycline at Low Concentrations - The Binh, Nguyen; Quang Dong, Nguyen (VNU Journal of Science: Mathematics - Physics, 2020)
We studied to produce SERS substrates using gold (Au) nanoparticles (AuNPs) prepared by pulse laser ablation (PLA) in water. The colloidal Au NPs with average size of 23nm were deposited on a silicon wafer to form AuNPs/Si SERS substrate. Malachite green was chosen as a test analyte to examine the sensitivity of the SERS substrates. The SERS enhancement factor of the AuNPs/Si was found to be about 10 6 .  The high sensitivity of the AuNPs/Si substrates was confirmed by the SERS spectra of malachite green detected with high quality at concentrations of 0.1ppm. The SERS substrates can detect SERS spectra of tetracycline at low concentrations of around 1ppm.